Systematic theology and climate change : ecumenical perspectives - Northcott, Michael S., editor (New York : Routledge, 2014)
Introduction / Michael S. Northcott and Peter M. Scott -- The Trinity / Timothy Gorringe -- Christology / Niels Henrik Gregersen -- Holy Spirit / Michael S. Northcott -- Creation / Celia Deane-Drummond -- Creatures / Rachel Muers -- Humanity / Peter M. Scott -- Sin and salvation / Neil Messer -- Church / Tamara Grdzelidze -- Eschatology / Stefan Skrimshire.